Impact of inorganic fertilizer to soil biological activity in an oil palm plantation. (October 2019) - Wahyuningsih, Resti; Marchand, Leo; Pujianto,; Suhardi,; Caliman, JP
Abstract: Oil palm can produce the highest quantity of vegetable oil per unit area. In order to reach this potential, as well as to maintain, and when necessary to improve the chemical fertility of soils, inorganic fertilizers are regularly applied in plantations. As it has been reported that the addition of inorganic fertilizers in agriculture, could negatively affect the biological characteristics of the soil, we have initiated a first research program to evaluate and confirm such possibility related to oil palm cultivation. This paper presents a study about the impact of inorganic fertilizer applications of soil biological activity in oil palm plantation located in the province of Riau in Sumatra, Indonesia. Observations have been conducted in a factorial NxPxK fertilizer trial, since 1995. For this study, our observations aimed to determine the short-term impact of these inorganic fertilizers, i.e. the impact during the following days after applications, as well as the long-term impact of similar fertilizers that have been applied repetitively, every six months since 1995. Bait lamina sticks were used to assess the biological soil activity (soil fauna feeding activity) from July to December 2017. Three types of fertilizer have been used for the study, Urea (as nitrogen source), Triple Super Phosphate (as phosphorus source) and Muriate of Potash (as potassium source) at various rates, and several combinations have been tested. The bait laminas were inserted in the palm circles, where fertilizers are commonly applied. The results show that in the short-term applications of inorganic fertilizers result in an increase of the soil fauna feeding activity: two days after urea applications, soil fauna feeding activity increased significantly compared the values before application. Phosphate and potassium fertilizer applications also increased the feeding activity, but this happened five days after the respective fertilizer applications. The intensity of the increase varied depending on the rate of applications. The long-term application of potassium fertilizer significantly increased the soil fauna feeding activity, while the application of phosphorus and nitrogen fertilizers did not show a significant increase.